Comparison of Community Leader Perceptions on Urban Forests in South Florida - Francisco Escobedo; Robert Northrop; Michael Orfanedes; Anna Iaconna (EDIS)
FOR230, a 4-page illustrated fact sheet by Francisco Escobedo, Robert Northrop, Michael Orfanedes, and Anna Iaconna, compares the results from a survey conducted in Broward and Hillsborough Counties in Florida. Includes references. Published by the UF School of Forest Resources and Conservation, December 2009.